Managing cooperative learning and digital competences in secondary education: a systematic review - Samane-Cutipa, Virginia A.; Callacondo Velarde, Juan Carlos; Rucano Paucar, Fabian Hugo; Talavera-Mendoza, Fabiola (Institute of Advanced Engineering and Science, 2025)
The COVID-19 pandemic led most schools to opt for distance education, resulting in challenges in the educational field. However, the increased use of digital technology prompted studies on strategies to help reduce the digital divide concerning two key 21st-century skills: cooperation and digital competencies. This article aims to analyze the study of cooperative learning in relation to the achievement of digital competencies in secondary education. It was developed through a systematic literature review (SLR) using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) methodology, retrieving scientific information from the Web of Science (WoS) and ERIC databases, published from 2018 to 2024. The results and findings emphasize the existence of strategies aimed at improving teaching and learning, academic performance, and students’ communication and social skills through task management, the formation of cooperative teams, and conflict resolution with shared leadership. Additionally, it highlights the development of digital competencies such as information retrieval, digital interaction, virtual object creation, digital security, and responsible citizenship. The conclusions focus on using cooperative learning strategies to make the teacher’s role more efficient in interactive spaces.